2017
DOI: 10.1186/s13395-017-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between changes in the 3D organization of the genome and transcription during myotube differentiation in vitro

Abstract: BackgroundThe spatial organization of eukaryotic genomes facilitates and reflects the underlying nuclear processes that are occurring in the cell. As such, the spatial organization of a genome represents a window on the genome biology that enables analysis of the nuclear regulatory processes that contribute to mammalian development.MethodsIn this study, Hi-C and RNA-seq were used to capture the genome organization and transcriptome in mouse muscle progenitor cells (C2C12 myoblasts) before and after differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 94 publications
1
45
0
Order By: Relevance
“…Unlike TADs, chromosomal A/B compartments have often been reported as highly variable between tissues or developmental stages, involving dynamic mechanisms of epigenetic control [51][52][53]. Here, we postulated that despite its plasticity, the structural organization in genome compartments for a given tissue could also be under selective pressure across a large phylogenetic spectrum.…”
Section: Comprehensive Maps Of Topological Domains and Genomic Comparmentioning
confidence: 87%
“…Unlike TADs, chromosomal A/B compartments have often been reported as highly variable between tissues or developmental stages, involving dynamic mechanisms of epigenetic control [51][52][53]. Here, we postulated that despite its plasticity, the structural organization in genome compartments for a given tissue could also be under selective pressure across a large phylogenetic spectrum.…”
Section: Comprehensive Maps Of Topological Domains and Genomic Comparmentioning
confidence: 87%
“…Comprehensive gene expression analyses have also shown that myogenic differentiation ensues in a stepwise fashion, where sequential activation of a specific set of genes restructures the cells one step at a time toward the differentiated phenotype [48]. Nonetheless, at the early stage of the differentiation, thousands of genes are differentially expressed [14,49,50], mostly within 24 hours of differentiation. As a result, epigenetic changes reflecting the alteration of gene programs should occur.…”
Section: Discussionmentioning
confidence: 99%
“…A recent low-resolution (400 kb) genome-wide analysis of chromatin interactions in myoblasts pre- and post-differentiation showed overall similarity in genome organization despite the change in differentiation state. The resolution achieved precluded identifying gene-specific interactions but nevertheless showed that differentiation did induce some compartment switching, indicating interconversion of specific regions of hetero- and euchromatin in myoblasts and myotubes (139). …”
Section: The Chromatin State At Active Myogenic Locimentioning
confidence: 99%